Inter-tree variability of autumn leaf phenology of European beech (Fagus sylvatica) on a site in Ljubljana, Slovenia - Škrk, Nina (Les (Ljubljana), 2020)
Temporal variability of leaf senescence (autumn phenology) was observed in 2020 in 11 European beech (Fagus sylvatica) trees in Tivoli, Rožnik and Šišenski hrib Landscape Park in Ljubljana, Slovenia, previously this year observed also for spring phenology. General leaf colouring (LC) BBCH94 occurred, between 19 and 24 October 2020, with lower inter-individual variability than that of leaf unfolding (LU), BBCH11. The trees had active leaves (LC-LU) between 177 and 199 days. In only 3 trees total leaf fall (LF), BBCH97, occurred before 19 November 2020. LC of the tree included in the long-term monitoring program of the Slovenian Environment Agency ARSO occurred on 24 October 2020. This is 7 days later than 65-year average of the same tree/location and is ascribed to weather conditions. Investigation of tree tissues showed that the width of the last formed tree-ring in the wood varied between 0.39 and 9.61 mm and in phloem between 0.09 and 0.26 mm and that the tissues reflect health condition of the trees.
Keywords: autumn; bukev; European beech; Fagus sylvatica; fenologija; inter-individual variability; jesen; leaf colouring; leaf fall; leaf phenology; nastajanje lesa; obarvanje listov; odpad listov; Slovenia; Slovenija; variabilnost med osebki; wood formation